Hubungan Intensitas Bullying Verbal Terhadap Internalisasi Nilai-Nilai Pendidikan Agama Islam pada Siswa Kelas XII - Laila Rahmi Hasanah; Mona Alyaa Sausan; Hartatiana; Muhammad Win Afgani (Tarbiyah bil Qalam : Jurnal Pendidikan Agama dan Sains, 2026)
This study investigates the relationship between the intensity of verbal bullying and the internalization of Islamic Religious Education (PAI) values among twelfth-grade students at a private Islamic high school in Palembang. The quantitative correlational survey method was used with a population of 48 students and purposive sampling. Data were collected through Likert-scale questionnaires, observations, and documentation. Descriptive and inferential statistical analyses, including Pearson correlation, were performed using SPSS 25. Results reveal that both verbal bullying intensity and internalization of PAI values fall into a moderate category. The Pearson correlation coefficient indicated a weak negative relationship (r = -0.126) that was statistically insignificant (p = 0.392). The conclusion emphasizes that verbal bullying does not significantly affect the internalization of Islamic values, suggesting that other ecological factors more strongly influence value internalization. These findings recommend a holistic approach in developing students’ character and spirituality in school environments.